The Neurodevelopmental Pathogenesis of Tuberous Sclerosis Complex (TSC) - Feliciano, David M. (Frontiers in Neuroanatomy, 2020)
Tuberous Sclerosis Complex (TSC) is a model disorder for understanding brain development because the genes that cause TSC are known, many downstream molecular pathways have been identified, and the resulting perturbations of cellular events are established. TSC therefore provides an intellectual framework to understand the molecular and biochemical pathways that orchestrate normal brain development.The TSC1 and TSC2 genes encode Hamartin and Tuberin which form a GTPase activating protein complex. Inactivating mutations in TSC genes (TSC1/TSC2) cause sustained Ras Homologue Enriched in Brain (RHEB) activation of the mammalian isoform of the Target of Rapamycin Complex 1 (mTORC1). TOR is a protein kinase that regulates cell size in many organisms throughout nature. mTORC1 inhibits catabolic processes including autophagy and activates anabolic processes including mRNA translation. mTORC1 regulation is achieved through two main upstream mechanisms. The first mechanism is regulation by growth factor signaling. The second mechanism is regulation by amino acids. Gene mutations that cause too much or too little mTORC1 activity lead to a spectrum of neuroanatomical changes ranging from altered brain size (micro and macrocephaly) to cortical malformations to Type I neoplasias. Because somatic mutations often underlie these changes, the timing and location of mutation results in focal brain malformations. These mutations therefore provide gain-of-function and loss-of-function changes that are a powerful tool to assess the events that have gone awry during development and to determine their functional physiological consequences. Knowledge about the TSC-mTORC1 pathway has allowed scientists to predict which upstream and downstream mutations should cause commensurate neuroanatomical changes. Indeed, many of these predictions have now been clinically validated. A description of clinical imaging and histochemical findings is provided in relation to laboratory models of TSC that will allow the reader to appreciate how human pathology can provide an understanding of the fundamental mechanisms of development.